Sistem Pendukung Keputusan Penentuan Kenaikan Gaji Karyawan (Kasus PPKS Marihat) - Batubara, Ela Roza; Poningsih, P (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
Determining employee salary increases is an important aspect of human resource management that influences employee motivation and productivity. This process is often complex and requires accurate evaluation of multiple criteria. This research aims to develop a decision support system (DSS) for determining employee salary increases using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. The MOORA method was chosen because of its ability to handle various criteria and provide objective results. This system is designed to help managers make faster and more precise decisions by considering various factors such as length of service, attendance and competency. The implementation of this system is expected to increase transparency and accuracy in the process of assessing employee salary increases, as well as reducing the potential for bias and subjectivity. Test results show that this system is effective in providing reliable recommendations for employee salary increase decisions. Thus, this MOORA-based decision support system can be a useful tool for companies in managing human resources more efficiently and fairly.